(untitled) (Psychology Travelogs, 2023)
The article presents the results of a theoretical analysis of the available definitions and models of providing psychological first aid (PFA). Common features in the definitions of PFA have been identified, its purpose and specifics of provision at different time intervals after a traumatic event have been determined. Such PFA models as RAPID PFA (by George S. Everly, Jr. and Jeffrey M. Lating) and MAASE (M. Farhi) are given and compared. Recommendations of Israeli specialists regarding the specifics of providing PFA in the acute period are presented. The main aspects of providing PFA have been determined. The theoretical analysis of the definitions and models of psychological first aid identified by us in the psychological literature showed that there are quite a lot of common features between them, in particular, PFA is usually provided in the first days after experiencing a traumatic event, the main purpose of PFA is to stabilize the condition of the victim and prevent development in her PTSD; providing PFA does not require a psychological education, but special training in PFA is necessary, in particular, the possession of a number of skills and abilities (active listening skills, symptom assessment skills, the ability to apply mental self-regulation techniques in appropriate situations and teach them to others, the ability to be directive and benevolent at the same time ). Among the considered PFA models, we identified the Israeli MAAS’E model of Dr. M. Farhi as the most effective in wartime due to its clarity, practicality, brevity, and verification by the conditions of war. Prospects for further research are seen in the practical adaptation and modification of the considered PFA models to the conditions of the war in Ukraine and the development of relevant practical recommendations for the provision of psychological first aid to the population of Ukraine.